"We can't just have a casual conversation": An institutional ethnography-informed study of work in labour and birth. (June 2021) - Brydges, Ryan; Nemoy, Lori; Campbell, Doug M.; Meffe, Filomena; Moscovitch, Linda; Fella, Sabina; Chandrasekaran, Nirmala; Bishop, Catherine; Khodadoust, Nazanin; Ng, Stella L.
Abstract: Labour and delivery units often become contested workplaces with tensions between obstetrics, nursing, and midwifery practices. These tensions can impede communication and raise concerns about provider wellness and patient safety. Remedying such tensions requires inquiry into the drivers of recurrent problems in interprofessional practice. We engaged in change-oriented inquiry informed by institutional ethnography (IE) within an academic hospital in Toronto, Canada (2017–2019). Clinicians identified critical incident analysis reports used to document recurrent issues for transfers of care (TOC) and consultations between professionals. We then mapped the everyday/everynight work of midwives, nurses, and obstetricians by observing (75 h) and interviewing them (n = 15). We also traced work processes to local (forms and hospital policies) and external (national policies and evidence-based guidelines) texts. Our IE-informed analysis made visible the otherwise hidden links between the everyday work of practitioners and its social organization. Three intrapartum work processes involving midwives consulting with obstetricians were identified: induction of labour with TOC back to midwife once labour was "active", consultation without TOC, and TOC for various indications. Three points of disjuncture complicated these processes: (i) a local "3 consult rule", linked to medico-legal governance and remuneration structures; (ii) subjective interpretations of the "4-cm dilation rule", a policy meant to standardize practice; and (iii) regulations delaying the timing of consultations. The Electronic Fetal Monitoring system served as a powerful text, materializing issues of professional scope and autonomy for midwives, and medicolegal accountability for obstetricians. Our study extends extant evidence that medicine-driven governance of midwifery practices can perpetuate interprofessional challenges. While practitioners spoke of the three disjunctures as 'laws', most also viewed them as ostensibly modifiable. Interprofessional tensions may be addressed by considering how social organization, materialized in texts detailing medico-legal liability and remuneration, can constrain possible practices through regulatory protocols, local ruling policies, and cultural expectations (e.g., documentation practices). Highlights: Medicine-driven governance of midwifery practices can perpetuate challenges. Electronic Fetal Monitoring acts as a text that materializes professional conflicts. Intersections of health and law underlie the observed social organization of work. Making disjunctures explicit can stimulate collaborative change.